Assessing food and nutrition literacy in children and adolescents: a systematic review of existing tools. Issue 4 (3rd April 2022) - Perreault, Maude; Ma, David WL; Haines, Jess
Abstract: Objective: Food literacy (FL) and nutrition literacy (NL) are concepts that can help individuals to navigate the current food environment. Building these skills and knowledge at a young age is important for skill retention, confidence in food practices and supporting lifelong healthy eating habits. The objectives of this systematic review were to: (i) identify existing tools that measure FL and NL among children and/or adolescents and (ii) describe the psychometric properties. Design: A 4-phase protocol was used to systematically retrieve articles. The search was performed in May 2021. Study characteristics and psychometric properties were extracted, and a narrative synthesis was used to summarise findings. Risk of bias was assessed using the COSMIN checklist. Setting: Six databases were searched to identify current tools. Participants: Children (2–12 years) and adolescents (13–18 years) participated in this study. Results: Twelve tools were identified. Three tools measured FL, 1 tool measured NL, 4 tools measured both FL and NL, and 4 tools measured subareas of NL—more specifically, critical NL, food label and menu board literacy. Most tools were self-reported, developed based on a theoretical framework and assessed some components of validity and/or reliability for a specific age and ethnic group. The majority of tools targeted older children and adolescents (9–18 years of age), and one tool targeted preschoolers (3–6 years of age). Conclusions: Most widely used definitions of FL and NL do not acknowledge life-stage specific criterion. Continued efforts are needed to develop a comprehensive definition and framework of FL and NL appropriate for children, which will help inform future assessment tools.